Teaching English through Silly Mistakes of the Students: An Action Research Bahadur Khatri - Khatri, Bahadur (International Journal For Research In Educational Studies, 2015)
Teachers’ frustration on students’ poor performance can lead the institution down. There can be several reasons behind the poor performance of the students; ignorance, carelessness, overgeneralization, hypercorrection, mother tongue interference, wrong input, and so on. Sometimes the students take some subjects very easily so they make several mistakes on such easy tasks. English language learning in English medium private schools is one example here. This study focuses on the problems raised from the English language teachers in a school. The students were taught English for several years but the mistakes on gender, number, concord and tense were found where teachers had not expected. The grammar teachers teach grammar in isolation. At the same time, other subjects’ teachers teach their subjects and search answers in content. In this regard, their grammar use in practice is somehow neglected. Negligence in study is very common in students (Newnham, 2000) which the teachers should recognize and eradicate if not possible, control and minimize in time otherwise it can create big problems in the future. For this, action research can be a good means to reach to the destination. Here students and teachers work together to bring change in existing problems. So, sometimes it is also called a participatory research.